Outrage - Kinahan, Deirdre (Nick Hern Books, 2022)
Outrage follows two sisters, Alice and Nell, who play key roles in organising civic resistance and the propaganda war. Like everyone else in Ireland, they become deeply conflicted as the country spins toward a devastating Civil War
10.5040/9781784607012.00000017
Keywords: Irish Civil War; National identity; Plays; Politics